A low-silicon Cu-ERI type molecular sieve-based monolithic foam catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202511950185.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-23
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-12-23
AI Technical Summary
但ERI型分子筛面临“硅铝比-稳定性-成本”三角矛盾:高硅体系(Si/Al>8)水热稳定性好,却需昂贵模板且晶化周期长;低硅体系(Si/Al<5)酸位与离子交换位丰富,低温活性高、温窗宽,但水热稳定性不足
[0020]优选的,S3中,所述硝酸铜溶液的浓度为0.1~2mol/L,浸渍处理温度为60~80 ℃,浸渍处理时间为6~12 h,浸渍处理次数为1次。
Smart Images

Figure CN121819918B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst technology, specifically relating to a low-silicon Cu-ERI type molecular sieve-based monolithic foam catalyst, its preparation method, and its application. Background Technology
[0002] Nitrogen oxides (NO) x Photochemical smog is the primary pollutant emitted by both stationary and mobile sources, and is also known as photochemical smog, acid rain, and PM2.5. 2.5 The key precursors formed pose a significant threat to human health and the ecological environment. Ammonia selective catalytic reduction (NH3-SCR) is widely recognized as the most mature and efficient NO reduction method under oxygen-rich conditions. x End-of-pipe treatment technologies. However, commercial V2O5–WO3 / TiO2 catalysts have a narrow operating temperature window (300–400℃), high vanadium toxicity, and poor hydrothermal stability. Developing green, efficient, and wide-temperature-window alternative materials is urgently needed.
[0003] Copper-based small-pore molecular sieves have become the benchmark material for NH3-SCR due to their wide-temperature activity, high N2 selectivity, excellent low-temperature performance, and outstanding hydrothermal stability. Currently, the only commercially available Cu-SSZ-13 requires the use of expensive and environmentally unfriendly N,N,N-trimethyl-1-adamantane ammonium hydroxide (TMAdaOH), significantly increasing costs and environmental impact. Therefore, constructing a new generation of molecular sieve catalysts that do not require organic templates and possess both high denitrification activity and hydrothermal stability has significant scientific and industrial value.
[0004] ERI (Erythritolite) possesses a three-dimensional eight-membered ring channel (3.6 × 5.1 Å), and its unique "cage-channel" structure can effectively suppress low-activity CuO. x Clustering enhances N2 selectivity, achieving SCR comparable to CHA. However, the synthetic window for pure-phase ERI is extremely narrow, and existing studies mostly rely on organic templates: Wang et al. from Tianjin University ( Micropor. Mesopor. Mater. (2019, 279, 407-415) Using N,N-dimethylpiperidinium hydroxide (DMPOH) as a template and FAU molecular sieve as a silica-alumina source for hydrothermal conversion; Zhu et al., University of Tokyo ( Adv. Sci. 2024, 11, 2307674; J. Catal. (2020, 391, 346-356) uses tetrapropylammonium hydroxide (TPAOH) and hexamethylammonium bromide (C 12 H 30 High-silicon ERI (Si / Al = 9.1) was prepared using a dual organic template (Br2N2). However, the above process has high template costs and a significant environmental impact, and the resulting Cu-ERI is mostly in the form of particles / powders, resulting in high bed pressure drop, making it difficult to scale up directly to industrial applications.
[0005] Monolithic catalysts can grow molecular sieve layers in situ on the support surface, offering advantages such as low pressure drop, high mechanical strength, and easy modular scaling. However, ERI-type molecular sieves face a "silicon-aluminum ratio-stability-cost" dilemma: high-silicon systems (Si / Al>8) have good hydrothermal stability but require expensive templates and have long crystallization cycles; low-silicon systems (Si / Al<5) have abundant acid sites and ion exchange sites, resulting in high low-temperature activity and a wide temperature window, but insufficient hydrothermal stability. Even more challenging is the tendency to generate OFF / ERI symbiotic phases or dense heterocrystalline layers under low-silicon conditions without organic templates, clogging pores. To date, the controllable construction of low-silicon pure-phase ERI on monolithic supports such as Al2O3 foam has not been achieved. Summary of the Invention
[0006] In view of this, this invention addresses the aforementioned bottlenecks by proposing a novel strategy for growing a low-silicon Cu-ERI monolithic catalyst on the surface of Al2O3 foam without an organic template, using ultrasonic-assisted rapid aging. This strategy aims to simultaneously solve four major challenges: low-cost synthesis, high activity, high stability, and low bed resistance, providing a catalyst suitable for both mobile and stationary NO sources. x Deep purification offers a new generation of technological solutions.
[0007] The technical solution of the present invention is as follows:
[0008] A low-silicon Cu-ERI type molecular sieve-based monolithic foam catalyst, the structure of which includes a supporting foam Al2O3 and an ERI molecular sieve membrane layer located on the foam Al2O3, wherein the ERI molecular sieve membrane layer contains Cu.
[0009] Preferably, the ERI molecular sieve membrane layer further contains F; the Cu:Al molar ratio is 0.18~0.28; the F:Si molar ratio is 0~0.06; and the Si:Al molar ratio is 2.9~3.7.
[0010] More preferably, the Cu:Al molar ratio is 0.18~0.28; the F:Si molar ratio is 0~0.06; and the Si:Al molar ratio is 2.9~3.7.
[0011] Preferably, the morphology of the ERI molecular sieve is rod-shaped, with a diameter of about 0.5 μm and a length of 15~18 μm; the thickness of the ERI molecular sieve membrane is 15~19 μm.
[0012] This invention discloses a method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst, characterized by comprising the following steps: S1. Prepare an impregnation solution containing ERI molecular sieve seeds, immerse Al2O3 foam in the impregnation solution, and dry it to obtain seeded Al2O3 foam. S2. Potassium hydroxide, sodium hydroxide, aluminum hydroxide, sodium fluoride, potassium fluoride, colloidal silica and water are mixed to form a mixed solution; the mixed solution is placed in an ultrasonic instrument and aged at room temperature to obtain a synthetic sol; the synthetic sol is crystallized with the seeded foam Al2O3 in S1, and washed with deionized water to obtain a 3D structured ERI@Al2O3 molecular sieve membrane. S3. The above molecular sieve membrane is introduced into a copper nitrate solution to obtain a monolithic Cu-ERI type molecular sieve catalyst.
[0013] This invention employs a two-stage hydrothermal synthesis method to construct a Cu-ERI film on an Al2O3 foam support using a fluorinated sol without organic template agents. The active metal component is then introduced via a simple ion exchange method. This catalyst exhibits a wide temperature conversion window in the NH3-SCR reaction, and particularly demonstrates excellent NO reduction even in complex systems containing SO2 and H2O. x Conversion rate.
[0014] Preferably, the molar ratio of each component in the preparation of ERI molecular sieve seed crystals is SiO2:Al2O3:K2O:TEAOH:C 12 H 30 Br2N2:H2O=1:0.03:0.09:0.8:0.13:25.
[0015] Preferably, the specific steps for preparing ERI molecular sieve seed crystals are as follows: Aluminum sec-butoxide is dissolved in tetraethylammonium hydroxide (TEAOH) to prepare an aluminum source solution; subsequently, colloidal silica is added dropwise to the aluminum source solution, and the solution is placed in an oil bath at 90°C and stirred for aging for 20 hours; after aging, potassium hydroxide and C are added sequentially to the solution. 12 H 30 The Br2N2 solution was then poured into a reaction vessel and reacted at 150°C for 120 hours. After the reaction was completed, the product was centrifuged, dried, and ground in sequence, and then calcined at 550°C for 10 hours to remove the template agent, thus obtaining the final product.
[0016] Preferably, in S1, the concentration of the seed crystal impregnation solution is 6~10 wt%, the number of impregnations is 1~3 times, and the solution is dried at 60-100℃.
[0017] Preferably, in S2, the molar ratio of the oxide forms of each component in the synthetic sol is SiO2:Al2O3:K2O:Na2O:H2O:(NaF+KF)=1:0.015:0.11:0.34:(80~200):(0~1). n (NaF) / n (KF)=3.
[0018] More preferably, the molar ratio of the oxide forms of each component in the synthetic sol is SiO2:Al2O3:K2O:Na2O:H2O:(NaF+KF)=1:0.015:0.11:0.34:(120~160):(0.8~1.0).
[0019] Preferably, in S2, the ultrasonic aging treatment power is 20 kHz, the temperature is room temperature, the treatment time is 1.0 h, the crystallization reaction temperature is 175℃, and the crystallization reaction time is 24 h.
[0020] Preferably, in step S3, the concentration of the copper nitrate solution is 0.1~2 mol / L, the immersion temperature is 60~80 ℃, the immersion time is 6~12 h, and the immersion is performed once.
[0021] More preferably, the concentration of the copper nitrate solution is 0.5~1.0 mol / L.
[0022] A third aspect of the invention provides the application of the catalyst in the NH3-SCR reaction.
[0023] This invention has at least one of the following beneficial effects: (1) The present invention uses an organic template-free fluorine-containing ultra-dilute sol method to grow a dense ERI-type crystal film on monolithic Al2O3 foam, eliminating the template removal step by firing, reducing raw material costs by more than 60%, and does not rely on external equipment (such as 3D printers), and has the advantages of simple operation and low cost.
[0024] (2) This invention achieves the growth of low-silicon ERI on Al2O3 foam for the first time, solving the problem that low-silicon gels are prone to generating OFF / ERI symbiotic phases or dense heterocrystalline layers.
[0025] (3) The present invention can produce ERI-type monolithic catalysts by both fluorine-containing and fluorine-free synthetic sols. In particular, the innovative introduction of fluorine ions into the synthetic sol effectively improves the stability of ERI crystals, giving them excellent water and sulfur resistance.
[0026] (4) The catalyst prepared by this invention differs from the traditional impregnation and coating method, possessing abundant catalytic active sites and exhibiting extremely high catalytic activity and stability. It is a novel catalyst with great development potential. In the selective catalytic reduction of NO by NH3... x In the (NH3-SCR) reaction, experimental data from this embodiment show that the catalyst achieves over 90% NO removal within a wide temperature range of 200–500 °C. xThe conversion rate is high, and the N2 selectivity is close to 100%. In addition, even in complex environments containing water and SO2, the catalyst still exhibits excellent catalytic performance, demonstrating excellent resistance to water and sulfur. With its template-free synthesis, high activity at low temperatures, and excellent resistance to sulfur and water, ERI-type molecular sieves have become the next-generation small-pore molecular sieve-based catalyst with the greatest industrialization potential in the NH3-SCR field after CHA. Attached Figure Description
[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0028] Figure 1 The images shown are (a) the seed crystals in Example 1 (with an inset image of its SEM image) and (b) the catalysts obtained in Comparative Example 1, X-ray diffraction (XRD) patterns.
[0029] Figure 2 The XRD patterns of the Al2O3 foam support, the catalysts obtained in Examples 1-4, and the catalyst obtained in Comparative Example 2 are shown.
[0030] Figure 3 The images shown are scanning electron microscope (SEM) images of the catalysts obtained in Examples 1-4 and Comparative Example 2; (a) and (b) are Comparative Example 2, (c) and (d) are Example 2, (e) and (f) are Example 3, (g) and (h) are Example 1, and (i) and (j) are Example 4.
[0031] Table 1 shows the EDX results of the catalysts obtained in Examples 1-4 and Comparative Example 2.
[0032] Figure 4 The graphs shown depict the denitrification performance of the catalysts obtained in Examples 1-4 and Comparative Example 2 in NH3-SCR. (a) shows the denitrification performance of NO. x (a) is the conversion rate of N2; (b) is the selectivity of N2.
[0033] Figure 5 The graphs shown below illustrate the denitrification performance of the catalysts obtained in Examples 5-7 and Comparative Example 2 in NH3-SCR. (a) shows the denitrification performance of NO. x (a) is the conversion rate; (b) is the selectivity of N2.
[0034] Figure 6 The denitrification performance of the catalysts obtained in Examples 8-10 and Comparative Example 2 in NH3-SCR is shown in the figure.
[0035] Figure 7The diagram shows the denitrification performance of the catalysts obtained in Examples 11-13 and Example 1 in NH3-SCR.
[0036] Figure 8 The figure shows the sulfur resistance performance of the catalysts obtained in Examples 1-4 and Comparative Example 2 in NH3-SCR.
[0037] Figure 9 The diagram shows the water resistance of the catalysts obtained in Examples 1-4 and Comparative Example 2 in NH3-SCR.
[0038] Figure 10 The figure shown is a graph illustrating the water and sulfur resistance of the catalyst obtained in Example 1 in NH3-SCR.
[0039] Figure 11 The figure shows the water and sulfur resistance performance of the catalyst obtained in Comparative Example 2 in NH3-SCR. Detailed Implementation
[0040] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0041] Example 1 A method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst, specifically including the following steps: Step 1: Dissolve 0.5 g of ERI molecular sieve seed crystals in 4.5 g of deionized water, stir until homogeneous, and then ultrasonically disperse for 10 minutes to obtain a uniform impregnation solution containing ERI molecular sieve seed crystals. Then, vertically and slowly immerse an Al2O3 foam (10 mm high, 10 mm diameter, from Chengjunda New Materials Technology Co., Ltd.) into the impregnation solution to ensure uniform seed crystal loading. After drying, repeat the impregnation process once more. Finally, dry at 80℃ for later use to obtain seeded Al2O3 foam.
[0042] The process of ERI molecular sieve seeding in step 1 is as follows: Aluminum sec-butoxide was dissolved in tetraethylammonium hydroxide (TEAOH) to prepare an aluminum source solution. Then, colloidal silica (containing 30% SiO2 by mass, Sigma-Aldrich) was added dropwise to the aluminum source solution, transferred to a PP bottle, and stirred thoroughly. The PP bottle was placed in an oil bath at 90°C and aged with stirring for 20 hours. After aging, potassium hydroxide and hexamethylammonium bromide (C...) were added sequentially to the solution. 12 H 30A Br2N2 solution was thoroughly mixed. Finally, the mixture was poured into a reaction vessel and reacted at 150°C for 120 hours. After the reaction, the product was centrifuged, dried, and ground sequentially, and then calcined at 550°C for 10 hours to remove the template agent, yielding the final product. The molar ratio of the oxide forms of each component in the synthetic sol was as follows: n (SiO2): n (Al2O3): n (K2O): n (TEAOH): n (C 12 H 30 Br2N2): n (H2O)=1:0.03:0.09:0.8:0.13:25.
[0043] Step 2: First, dissolve potassium hydroxide (KOH), sodium hydroxide (NaOH), sodium fluoride (NaF), potassium fluoride (KF), and aluminum hydroxide sequentially in deionized water. Stir until the solution is clear. Then, slowly add colloidal silica (containing 30% SiO2 by mass, Sigma-Aldrich) dropwise to form a synthetic sol. The molar ratio of each component in oxide form is as follows: n (SiO2): n (Al2O3): n (K2O): n (Na2O): n (H2O): n (NaF+KF)=1:0.015:0.11:0.34:120:0.8, n (NaF) / n (KF)=3; Subsequently, the mixed solution was placed in an ultrasonic instrument for ultrasonic aging at room temperature. The ultrasonic aging power was 20 kHz, the temperature was room temperature, and the treatment lasted for 1 h.
[0044] The aged synthetic sol and the seeded Al2O3 foam support from step 1 were placed together in a reactor and crystallized at 175°C for 24 hours. After the reaction, the sample was rinsed with deionized water until neutral and dried to obtain the product ERI@Al2O3 molecular sieve membrane. Step 3: The above ERI@Al2O3 molecular sieve membrane was placed in 100 mL of a 1.0 mol / L copper nitrate solution and stirred continuously at 80 °C for 6 hours. After the reaction was completed, the sample was rinsed with deionized water until neutral and then dried to obtain the monolithic Cu-ERI foam catalyst.
[0045] Example 2 A method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst, which has the same steps as in Example 1, except that step 2 in Example 1 is modified accordingly. n (NaF+KF) / n When (SiO2) is changed to 0.1, the catalyst is finally obtained.
[0046] Example 3 A method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst, which has the same steps as in Example 1, except that step 2 in Example 1 is modified accordingly. n (NaF+KF) / n When (SiO2) is changed to 0.3, the catalyst is finally obtained.
[0047] Example 4 A method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst, which has the same steps as in Example 1, except that step 2 in Example 1 is modified accordingly. n (NaF+KF) / n When (SiO2) is changed to 1.0, the catalyst is finally obtained.
[0048] The molar ratios of each element in the catalysts prepared in Examples 1-4 and Comparison 2 are shown in Table 1.
[0049] Table 1
[0050] Example 5 A method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst, which has the same steps as in Example 1, except that the sol-gel ratio in step 2 of Example 1 is changed to... n (SiO2): n (Al2O3): n (K2O): n (Na2O): n (H2O) = 1:0.015:0.11:0.34:80, and finally the catalyst is obtained.
[0051] Example 6 A method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst, which has the same steps as in Example 1, except that the sol-gel ratio in step 2 of Example 1 is changed to... n (SiO2): n (Al2O3): n (K2O): n (Na2O): n(H2O) = 1:0.015:0.11:0.34:160, and finally the catalyst is obtained.
[0052] Example 7 A method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst, which has the same steps as in Example 1, except that the sol-gel ratio in step 2 of Example 1 is changed to... n (SiO2): n (Al2O3): n (K2O): n (Na2O): n (H2O) = 1:0.015:0.11:0.34:200, and finally the catalyst is obtained.
[0053] Example 8 A method for preparing a low-silicon Cu-ERI molecular sieve-based monolithic foam catalyst is disclosed. The steps are consistent with those in Example 5, except that the concentration of copper nitrate in step 3 of Example 5 is changed to 0.1 mol / L, and the catalyst is finally obtained.
[0054] Example 9 A method for preparing a low-silica Cu-ERI molecular sieve-based monolithic foam catalyst is provided, which has the same steps as in Example 5, except that the concentration of copper nitrate in step 3 of Example 5 is changed to 0.5 mol / L, and the catalyst is finally obtained.
[0055] Example 10 A method for preparing a low-silicon Cu-ERI molecular sieve-based monolithic foam catalyst is disclosed. The steps are consistent with those in Example 5, except that the concentration of copper nitrate in step 3 of Example 5 is changed to 2.0 mol / L, and the catalyst is finally obtained.
[0056] Example 11 A method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst, which has the same steps as in Example 1, except that the sol-gel ratio in step 2 of Example 1 is changed to... n (H2O): n (SiO2)=80, and finally a catalyst is obtained.
[0057] Example 12 A method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst, which has the same steps as in Example 1, except that the sol-gel ratio in step 2 of Example 1 is changed to... n (H2O): n (SiO2)=160, and the catalyst was finally obtained.
[0058] Example 13 A method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst, which has the same steps as in Example 1, except that the sol-gel ratio in step 2 of Example 1 is changed to... n (H2O): n (SiO2)=200, and finally a catalyst is obtained.
[0059] Comparative Example 1 A method for preparing a low-silicon Cu-ERI type molecular sieve-based monolithic foam catalyst is provided. The preparation steps are consistent with those in Example 1, except that the seed coating in step 1 is not performed. That is, the Al2O3 foam is not impregnated in the seed impregnation solution, but is directly used in step 2.
[0060] The results are as follows Figure 1 As shown in b. From the corresponding XRD pattern, the diffraction peaks that appear are only for the Al2O3 foam support, and no obvious molecular sieve diffraction peaks were observed, indicating that the product is amorphous, which means that a crystalline film cannot be formed without the addition of ERI seeds.
[0061] In addition, from Figure 1 The XRD and SEM images of the ERI seed crystals in a show that the ERI seed crystals are elliptical in shape and have a size of approximately 200 nm × 500 nm.
[0062] Comparative Example 2 A method for preparing a low-silica Cu-ERI type molecular sieve-based monolithic foam catalyst is disclosed. The preparation steps are consistent with those in Example 1, except that step 2 in Example 1 is modified accordingly. n (NaF+KF) / n When (SiO2) is changed to 0, a fluorine-free catalyst is finally obtained.
[0063] Example 14 This embodiment analyzes the characterization data of the catalysts prepared in Examples 1-4, and the specific results are as follows: Figure 2 The images shown are X-ray diffraction patterns of the catalysts obtained in Examples 1-4 and Comparative Example 2 of this invention. Figure 2 As can be seen from the XRD patterns, the XRD diffraction peaks of all samples are consistent with the standard characteristic diffraction peaks of the Al2O3 support and the ERI-type molecular sieve, with no other impurity phases. This indicates that we have successfully synthesized the ERI-type molecular sieve film on the Al2O3 support. Meanwhile, no diffraction peaks of Cu species were observed in the XRD patterns. This also suggests that Cu species may be uniformly dispersed in the crystal framework in the form of oxide clusters or ions, without altering its crystal structure.
[0064] Figure 3The images shown are scanning electron microscope (SEM) images of the catalysts obtained in Examples 1-4 and Comparative Example 2. Figure 3 As shown in a and 3b, the surface of the fluorine-free film is completely covered by many rod-shaped crystals, each with a diameter of about 0.2 μm and a length of about 5 μm. These rod-shaped crystals form a continuous and relatively dense film with a thickness of about 18 μm; when a small amount of fluoride ions are introduced into the synthetic sol ( n (F - ) / n (SiO2)=0.1)( Figure 3 In cases c and 3d), the film surface still consists of rod-shaped crystals, but the number of crystals is reduced, and the film is not as continuous and dense, with noticeable pores visible. This is consistent with... Figure 2 The observed decrease in crystallinity in the corresponding XRD results is consistent with the phenomenon observed in the film, which is approximately 15 μm thick. As more fluoride ions are introduced into the synthetic sol, the rod-shaped crystals gradually aggregate and become longer. n (F - ) / n When the SiO2 concentration increases to 0.8, the crystals form relatively distinct rod-shaped bundles with a diameter of approximately 0.5 μm and a length reaching 15 μm. Figure 3 g and 3h); further increase in fluoride ions (g and 3h); n (F - ) / n (SiO2)=1.0), the rod-shaped crystal bundles continue to grow, still 0.5 μm in diameter, but with a length of 18 μm. The film thickness remains basically between 17 and 19 μm (e.g., SiO2=1.0). Figure 3 (as shown in f, 3h, and 3j).
[0065] Example 15 The catalysts prepared in Examples 1-7 and Comparative Example 2 of this invention were applied to the NH3-SCR reaction. The specific process is as follows: The catalyst was placed directly into a quartz tube (5 mm inner diameter, 500 mm length) for testing. To ensure accuracy, the catalyst was placed in the middle of the quartz tube, above the thermocouple, and the furnace temperature was controlled by a temperature control system, with a test temperature range of 100–600 °C. The simulated flue gas was [NO] = [NH3] = 500 ppm, 5% O2 (volume fraction), with N2 as the balance gas. The total gas flow rate was set to 100 mL / min, and the calculated GHSV was 60,000 h⁻¹. -1 Before testing, the simulated flue gas was thoroughly mixed in a mixer, and after stabilization, it was bypassed and introduced into the flue gas analyzer to record NO. xThe total intake value of (NO and NO2) was then transferred to the reaction path. After stabilization, the temperature was increased, and data was recorded every 50°C. To ensure the reaction reached a stable state, NO was recorded after holding at each target temperature for 20-30 minutes. x The outgassing values of NH3 and N2O are shown in the figure. Figure 4 and Figure 5 .
[0066] Figure 4 The catalytic performance of all catalysts in Examples 1-4 in the NH3-SCR reaction is compared. When comparing the Cu-ERI membrane without fluorine on the Al2O3 foam support in Comparative Example 2, NO2 content is significantly higher in the temperature range of 200-500 °C. x The conversion rate is nearly 100%, especially at a low temperature of 150℃ for NO. x The conversion rate was as high as 85%, and the N2 selectivity was close to 100%; while in Examples 2 and 3 n (F - ) / n When Cu-ERI films were synthesized with SiO2 at concentrations of 0.1 and 0.3, NO was also detected in the medium-high temperature region (200~450 ℃). x The conversion rate is close to 100%. Meanwhile, NO... x The conversion rate was higher than that of Comparative Example 2. As more fluoride ions were introduced into the synthetic sol, the Cu-ERI membranes obtained in Examples 1 and 4 remained unchanged except for a slight decrease in the low temperature region, and the N2 selectivity of all catalysts was close to 100, showing the best denitrification performance.
[0067] Figure 5 The catalytic performance of all catalysts in Examples 6-7 and Comparative Example 2 in the NH3-SCR reaction is shown. Compared with the catalyst in Comparative Example 2, when... n (H2O) / n When (SiO2) = 80 and 160, the prepared catalysts exhibit NO activity in the low-temperature region. x The conversion rates are basically similar, while NO in the high-temperature zone x However, the conversion rate decreased by approximately 18%; further improvement n (H2O) / n When (SiO2)=200, the obtained catalyst only produces NO within a narrow temperature range of 250~350 ℃. x The conversion rate exceeds 90%, which does not affect the selectivity of N2.
[0068] Figure 6 The catalytic performance of all catalysts in Examples 8-10 and Comparative Example 2 in the NH3-SCR reaction is shown. Compared with the catalyst in Comparative Example 2, the prepared catalysts showed better performance in the low-temperature region (≤150℃) and the high-temperature region (≥450℃) at lower initial copper ion concentrations.x The conversion rates of both decreased by 10-20%, while when the initial copper ion concentration was further increased to 2 mol / L, the NOx conversion rate of the prepared catalyst remained basically unchanged in the high-temperature region, but decreased in the low-temperature region. x The conversion rate decreased by about 30%.
[0069] Figure 7 The catalytic performance of all catalysts in Examples 11-13 and Example 1 in the NH3-SCR reaction is compared. All catalysts were tested over a wide temperature window (200-500°C) for NO. x The conversion rate is greater than 90%, especially for more dilute sols (Examples 12 and 13), and the resulting catalysts exhibit NO content in both low-temperature (≤150°C) and high-temperature (≥500°C) regions. x The conversion rates were all increased by about 10%, demonstrating the promoting effect of dilute sol on the denitrification performance of the catalyst.
[0070] Example 16 The catalysts prepared in Examples 1-4 and Comparative Example 2 of this invention were applied to water and sulfur resistance tests in the NH3-SCR reaction. The specific process is as follows: To test the water and sulfur resistance of the denitrification catalyst, 100 ppm SO2 and 5 vol% H2O (water vapor) were introduced into simulated flue gas, and flue gas analyzer readings were recorded at different times. H2O in the simulated flue gas was carried away from the heated steam generator via N2. The actual heating temperature of the steam generator could be calculated using a table of saturated steam pressure and water content at different temperatures and the Clapeyron equation. When no water resistance test was performed, N2 did not pass through the pipe containing the steam generator; its flow was controlled by switching a three-way valve. If 100 ppm SO2 and 5 vol% H2O were introduced simultaneously, NH4HSO4 and NH4HSO3 would easily form, covering the catalyst and clogging the pipes. These substances can decompose above 150 °C. Therefore, to ensure denitrification efficiency and prevent pipe blockage, the temperatures of the upper, lower, and standby pipes were set to 120 °C, 160 °C, and 160 °C, respectively, to decompose nitrates and nitrites. The results are shown in [Figure showing the results]. Figures 8-10 .
[0071] Figure 8 and Figure 9 The Cu-ERI@Al2O3 catalysts in Examples 1-4 exhibited excellent resistance to water and sulfur under simulated flue gas conditions. In an atmosphere containing only 100 ppm SO2 or 5 vol% H2O, all catalysts showed low NO levels across the entire temperature range. x The conversion rate remained stable throughout, and showed a significant improvement at high temperatures (>500 ℃). Particularly in tests containing 5 vol% H2O, the NO conversion rate at high temperatures (>500 ℃) was significantly higher. xThe conversion rate can reach 100%.
[0072] Figure 10 The performance of Example 1 was further demonstrated when 100 ppm SO2 and 5 vol% H2O were simultaneously introduced at 150°C. NO2 levels were significantly lower when only 100 ppm SO2 was introduced. x The conversion rate was unaffected; however, when only 5% H2O was introduced, the conversion rate decreased by approximately 30%, but the performance quickly recovered to the initial level after the H2O was stopped. When SO2 and H2O coexist, NO... x The conversion rate dropped by about 35%, but recovered quickly after the inflow was stopped.
[0073] In contrast, the fluorine-free catalyst in Comparative Example 2 showed NO levels in a 100 ppm SO2 atmosphere. x The conversion rate was stable, but in a 5 vol% H2O atmosphere, NO only increased at 200–350 °C. x The conversion rate remained stable, but decreased by approximately 10-30% at other temperature points. When SO2 and H2O were introduced simultaneously (e.g., ...), the conversion rate remained stable, while it decreased by approximately 10-30% at other temperature points. Figure 11 As shown), low temperature zone (≤200℃) NO x The conversion rate also decreased by 10-15%. Therefore, the low-silicon Cu-ERI monolithic foam catalyst synthesized in this invention exhibits significant advantages in water and sulfur resistance, and can maintain high-efficiency denitrification performance under complex operating conditions.
[0074] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a Cu-ERI type molecular sieve-based monolithic foam catalyst, characterized in that, Includes the following steps: S1. Prepare an impregnation solution containing ERI molecular sieve seeds, immerse Al2O3 foam in the impregnation solution, and dry it to obtain seeded Al2O3 foam. S2. Potassium hydroxide, sodium hydroxide, aluminum hydroxide, sodium fluoride, potassium fluoride, colloidal silica, and water are mixed to form a mixed solution; the mixed solution is placed in an ultrasonic instrument and aged at room temperature to obtain a synthetic sol; the molar ratio of each component in the synthetic sol is SiO2:Al2O3:K2O:Na2O:H2O:(NaF+KF)=1:0.015:0.11:0.34:(120~160):(0.8~1.0), n (NaF) / n (KF)=3; The synthetic sol was crystallized with the seeded foam Al2O3 in S1, and after washing with deionized water, a 3D structured ERI@Al2O3 molecular sieve membrane was obtained. S3. Immerse the above molecular sieve membrane in copper nitrate solution to obtain a monolithic Cu-ERI type molecular sieve catalyst; The Si:Al molar ratio in Cu-ERI type molecular sieve-based monolithic foam catalysts is 2.9~3.
7.
2. The preparation method according to claim 1, characterized in that, The molar ratio of each component in the preparation of ERI molecular sieve seed crystals is SiO2:Al2O3:K2O:TEAOH:C 12 H 30 Br2N2:H2O=1:0.03:0.09:0.8:0.13:25; The specific steps for preparing ERI molecular sieve seed crystals are as follows: aluminum sec-butoxide is dissolved in tetraethylammonium hydroxide (TEAOH) to prepare an aluminum source solution; then, colloidal silica is added dropwise to the aluminum source solution, and the solution is placed in an oil bath at 90°C and stirred for 20 hours to age. After aging is complete, potassium hydroxide and C are added to the solution in sequence. 12 H 30 The Br2N2 solution was then poured into a reaction vessel and reacted at 150°C for 120 hours. After the reaction was completed, the product was centrifuged, dried, and ground in sequence, and then calcined at 550°C for 10 hours to remove the template agent, thus obtaining the final product.
3. The preparation method according to claim 1, characterized in that, In S1, the concentration of the seed crystal impregnation solution is 6~10wt%, the number of impregnations is 1~3 times, and it is dried at 60~100℃.
4. The preparation method according to claim 1, characterized in that, In S2, the ultrasonic aging treatment frequency was 20 kHz, the temperature was room temperature, the treatment time was 1.0 h, the crystallization reaction temperature was 175℃, and the crystallization reaction time was 24 h.
5. The preparation method according to claim 1, characterized in that, In S3, the concentration of the copper nitrate solution is 0.1~2.0 mol / L, the immersion temperature is 60~80 ℃, the immersion time is 6~12 h, and the immersion treatment is performed once.
6. The Cu-ERI type molecular sieve-based monolithic foam catalyst prepared by the preparation method according to any one of claims 1 to 5.
7. The application of the catalyst according to claim 6 in the NH3-SCR reaction.